ANALISIS POTENSI DAN DAYA SAING KECAMATAN SEBAGAI PUSAT PERTUMBUHAN SATUAN WILAYAH PENGEMBANGAN (SWP) KABUPATEN MALANG - Sutikno, -; Maryunani, - (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2007)
In terms of administration, Malang is divided into two regions, Malang City andMalang Regency. Although the regions are different, economically two regionscan not separated because almost all economic activities are concentrated atMalang City. This has impacts on the economic gap between Malang City andMalang Regency. With respect to gap, the research was conducted to analyze thegrowth center of Regional Development Unit (RDU) of the Malang City, based ontwo development directions: identifying sectoral economic potentials and thatfor regional sowol potentials.In terms of regional aspects, the description of development centers in each RDUare: (1) Ngantang Sub-district is a priority for the development center of RDU I;(2) Singosari Sub-district is a priority for the development center of northernRDU II; (3) Pakisaji Sub-district is a priority for the development center ofsouthern RDU II; (4) Poncokusumo Sub-district is a priority for the developmentcenter of RDU IV; (5) Kepanjen Sub-district is a priority for the developmentcenter of RDU V; (6) Pagelaran Sub-district is a priority for the developmentcenter of RDU VII; and (7) Turen Sub-district is a priority for the developmentcenter of RDU VIII.Since the results has policy impacts, the government of the Malang Regencyshould decide regional development policies referring to the regionaldevelopment concept based on the economic and regional potentials so that itcan give priorities to potential districts to be acted as development centers. Byimplementing the policy, it is expected that economic activities will not beconcentrated on one development point, the Malang City as the only developmentpoint.Keywords: growth center, Regional Development Unit (RDU), sectoral economicpotentials and regional potentials